The Effect of POE Learning Strategy Assisted by Edmodo On Eco literation In Elementary School - Yuniar, Yuyun; Sopandi, Wahyu; Sujana, Atep (International Conference on Elementary Education, 2021)
This study aims to examine the effect of learning predict observe and explain (POE) during the Covid-19 assisted by Edmodo on the environmental literacy of grade VI elementary school students. The research method used was a quasi-experimental non-equivalent control group design with a control and experimental group design. The subjects studied were sixth-grade students at a school in Bandung, which was divided into two into the experimental group (28 students) and the control group (28 students). The experimental group received Edmodo-assisted POE while the control group received Direct Instruction (DI). Eco literacy is measured by multiple-choice questions. Environmental care attitudes were compiled with an attitude questionnaire. The analysis using SPSS for Windows version 22 and excel. The results showed that there were differences in Eco literacy skills between the experimental class and the control class with the mean paired differences between the pre-test and post-test for the experimental class was 22, the significance value (2-tailed) was 0,000 and the t-test result was 0.482. In addition to differences in post-test results, Edmodo-assisted POE learning has a positive effect on environmental literacy which is shown by N- gain 72, 37% is in the high category with moderate effectiveness with a minimum N-Gain score of 50% and a maximum N-gain of 100% and medium criteria for the attitudes and environmental sensitivity domains with an average Likert scale of 34%.